Isosorbide ester grafted bentonite modified polyvinyl chloride and preparation method thereof
Through the grafting reaction of isosorbate and bentonite, isosorbate grafted bentonite is formed and blended with polyvinyl chloride, which solves the problem of insufficient toughness of polyvinyl chloride and significantly improves its mechanical properties and toughness.
Patent Information
- Application Number
- CN202411775770.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-02-07
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The poor toughness of polyvinyl chloride limits its application range in pipes, profiles and boards.
Isosorbate grafted bentonite is formed by grafting isosorbate and blending it with polyvinyl chloride to form isosorbate grafted bentonite modified polyvinyl chloride.
This method effectively improves the mechanical properties and toughness of polyvinyl chloride, avoids the agglomeration of nano-bentonite, achieves uniform dispersion, forms a network structure to absorb external forces, and enhances the material's stress resistance.
Smart Images

Figure CN119391107A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polyvinyl chloride, in particular to isosorbide ester grafted bentonite modified polyvinyl chloride and a preparation method thereof. Background Art
[0002] Polyvinyl chloride, as one of the earliest industrialized general-purpose plastics, is one of the five general-purpose resins, and its output is second only to polyethylene. As polymer materials gradually replace traditional metal materials and wood, chemical building materials are widely used and promoted, and the requirements for polymer materials are getting higher and higher. Polyvinyl chloride is widely used in pipes, profiles, and plates. However, due to the disadvantages of polyvinyl chloride such as difficulty in processing and brittleness, its application range is greatly limited. It is of great research value to develop a method of toughening polyvinyl chloride polymer materials with low cost and good effect.
[0003] The traditional method of toughening polyvinyl chloride is by adding elastomer rubber, etc. This method can effectively improve the toughness of the matrix, but to a certain extent limits its oxidation resistance and heat resistance. Chinese patent CN102995445B discloses a polyvinyl chloride synthetic leather modified with attapulgite and bentonite. By modifying the formula and process and adding modified nano-inorganic materials, the flexibility of the synthetic leather is increased. A single nano-inorganic material has certain limitations on improving the toughness of polyvinyl chloride. The matrix is modified by adding isosorbide esters containing flexible long chains, and the polyvinyl chloride material obtained after mixing has excellent mechanical properties. Summary of the invention
[0004] In view of the deficiencies in the prior art, the present invention provides an isosorbide ester grafted bentonite modified polyvinyl chloride and a preparation method thereof, which solves the problem of poor toughness of polyvinyl chloride.
[0005] To achieve the above object, the present invention provides the following technical solution: an isosorbide grafted bentonite modified polyvinyl chloride, the isosorbide grafted bentonite modified polyvinyl chloride and the preparation method are as follows: (1) Ultrasonic dispersion of ethanol solvent, nano-bentonite and 3-glycidyloxypropyltrimethoxysilane, and a modification reaction at 60-80° C. for 24-36 hours in a nitrogen atmosphere, to obtain epoxy-modified bentonite after the reaction is completed; (2) Ethanol and deionized water are mixed evenly, and then 11-aminoundecanoic acid, epoxy-modified bentonite and sodium carbonate are added, and the mixture is stirred and mixed evenly to cause a ring-opening reaction. After the reaction is completed, amino acid-modified bentonite is obtained; (3) Toluene solvent, amino acid modified bentonite, p-toluenesulfonic acid and isosorbide dodecanoate are mixed evenly. The molecular formula of isosorbide dodecanoate is C 18 H 32O5, heating in a nitrogen atmosphere to cause an esterification reaction, and after the reaction is completed, isosorbide ester-grafted bentonite is obtained; (4) Premixing polyvinyl chloride, isosorbide grafted bentonite, calcium stearate and polysiloxane at 90-130° C. After premixing, transferring to a twin-roll plasticizer for melt blending, after blending, hot pressing on a flat vulcanizer, and cooling to obtain isosorbide grafted bentonite modified polyvinyl chloride.
[0006] Preferably, in step (1), the mass ratio of ethanol, nano-bentonite and 3-glycidyloxypropyltrimethoxysilane is 2500-6500:100:350-600.
[0007] Preferably, in step (2), the mass ratio of ethanol, deionized water, 11-aminoundecanoic acid, epoxy-modified bentonite and sodium carbonate is 1500-4000:1000-2500:150-280:100:8-15.
[0008] Preferably, the temperature of the ring-opening reaction in step (2) is 45-65° C., and the time of the ring-opening reaction is 15-30 h.
[0009] Preferably, in step (3), the mass ratio of toluene solvent, amino acid-modified bentonite, p-toluenesulfonic acid and isosorbide dodecanoate is 1200-2500:100:2-6:60-90.
[0010] Preferably, the temperature of the esterification reaction in step (3) is 150-180° C., and the time of the esterification reaction is 12-18 hours.
[0011] Preferably, in step (4), the mass ratio of polyvinyl chloride, isosorbide grafted bentonite, lubricant calcium stearate and defoaming agent polysiloxane is 100:15-30:1-3:0.5-2.
[0012] Preferably, the temperature of melt blending in step (4) is 120-150° C., and the time of melt blending is 5-8 min.
[0013] Compared with the prior art, the present invention has the following beneficial technical effects: The isosorbide grafted bentonite modified polyvinyl chloride comprises the following steps: in an experiment, 3-glycidyloxypropyltrimethoxysilane is first used to modify nano bentonite to obtain epoxy-modified bentonite; epoxy groups on the epoxy-modified bentonite and amino groups on 11-aminoundecanoic acid undergo epoxy ring-opening reaction to obtain amino acid-modified bentonite; carboxyl groups on the amino acid-modified bentonite and hydroxyl groups on isosorbide dodecanoate undergo esterification reaction under the action of p-toluenesulfonic acid as a catalyst to obtain isosorbide grafted bentonite; the isosorbide grafted bentonite is used as a toughening agent, polyvinyl chloride is used as a matrix, and mixed with a lubricant and a defoamer to obtain isosorbide grafted bentonite modified polyvinyl chloride.
[0014] The isosorbide ester grafted bentonite modified polyvinyl chloride, the nano bentonite has a layered structure, excellent mechanical properties and thermodynamic properties, is grafted onto isosorbide by a grafting method, effectively avoids the agglomeration of the nano bentonite, can be uniformly dispersed in the polyvinyl chloride matrix to form a network structure, can effectively eliminate stress when subjected to external force, and improve the mechanical properties of the polyvinyl chloride, isosorbide has excellent thermal stability, biocompatibility and degradability, and after being grafted with amino acids, a flexible long chain is introduced, which can effectively improve the toughness of the matrix, and the cyclic groups contained can generate interaction forces with hydrogen atoms in the polyvinyl chloride matrix, increase the free volume between polymer molecules, and can absorb a large amount of energy when subjected to external force, effectively improve the mechanical properties of the matrix, and greatly improve the toughness. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 It is a schematic diagram of the structure of isosorbide dodecanoate. DETAILED DESCRIPTION
[0016] To achieve the above object, the present invention provides the following specific implementation methods and examples: A method for preparing isosorbide grafted bentonite modified polyvinyl chloride is as follows: (1) adding ethanol solvent, nano-bentonite and 3-glycidyloxypropyltrimethoxysilane in a mass ratio of 2500-6500:100:350-600 to a reaction container, uniformly dispersing by ultrasonication, and carrying out a modification reaction at 60-80° C. for 24-36 hours in a nitrogen atmosphere. After the reaction is completed, centrifuging, washing with ethanol and deionized water, and drying to obtain epoxy-modified bentonite; (2) Adding ethanol solvent, deionized water solvent, 11-aminoundecanoic acid, epoxy-modified bentonite and sodium carbonate in a mass ratio of 1500-4000:1000-2500:150-280:100:8-15 into a reaction container in sequence, stirring and mixing evenly, and performing a ring-opening reaction at 45-65° C. for 15-30 hours. After the reaction is completed, washing with deionized water and methanol, and drying to obtain amino acid-modified bentonite; (3) adding toluene solvent, amino acid-modified bentonite, p-toluenesulfonic acid and isosorbide dodecanoate in a mass ratio of 1200-2500:100:2-6:60-90 into a reaction container, heating the mixture in a nitrogen atmosphere at 150-180° C. for 12-18 hours to cause an esterification reaction. After the reaction is completed, cooling the mixture, washing with sodium bicarbonate solution and deionized water, separating and drying the mixture to obtain isosorbide ester-grafted bentonite; (4) Add polyvinyl chloride, isosorbide grafted bentonite, calcium stearate and polysiloxane in a mass ratio of 100:15-30:1-3:0.5-2 into a reaction container in sequence. After premixing at 90-130° C., transfer the mixture to a twin-roll mill for melt blending at a temperature of 120-150° C. for 5-8 min. After blending, perform hot pressing on a flat vulcanizer and, after cooling, obtain isosorbide grafted bentonite modified polyvinyl chloride. Example 1
[0017] (1) adding ethanol solvent, nano-bentonite and 3-glycidyloxypropyltrimethoxysilane in a mass ratio of 2500:100:350 to a reaction container in sequence, uniformly dispersing by ultrasonication, and carrying out a modification reaction at 60°C for 24 hours in a nitrogen atmosphere. After the reaction is completed, centrifuging, washing with ethanol and deionized water, and drying to obtain epoxy-modified bentonite; (2) Adding ethanol solvent, deionized water solvent, 11-aminoundecanoic acid, epoxy-modified bentonite and sodium carbonate in a mass ratio of 1500:1000:150:100:8 into a reaction container in sequence, stirring and mixing evenly, and performing a ring-opening reaction at 45° C. for 15 hours. After the reaction is completed, washing with deionized water and methanol, and drying to obtain amino acid-modified bentonite; (3) adding toluene solvent, amino acid-modified bentonite, p-toluenesulfonic acid and isosorbide dodecanoate in a mass ratio of 1200:100:2:60 into a reaction container, heating the mixture in a nitrogen atmosphere at 150° C. for 12 hours to cause an esterification reaction. After the reaction is completed, cooling the mixture, washing with sodium bicarbonate solution and deionized water, separating and drying the mixture to obtain isosorbide ester-grafted bentonite; (4) Polyvinyl chloride, isosorbide grafted bentonite, calcium stearate and polysiloxane in a mass ratio of 100:15:1:0.5 were added to a reaction container in sequence. After premixing at 90° C., the mixture was transferred to a twin-roll mill for melt blending. The melt blending temperature was 120° C. and the melt blending time was 5 min. After blending, the mixture was hot-pressed on a flat vulcanizer. After cooling, isosorbide grafted bentonite modified polyvinyl chloride was obtained. Example 2
[0018] (1) adding an ethanol solvent, nano-bentonite and 3-glycidyloxypropyltrimethoxysilane in a mass ratio of 3500:100:420 to a reaction container in sequence, uniformly dispersing by ultrasonication, and carrying out a modification reaction at 65°C for 28 hours in a nitrogen atmosphere. After the reaction is completed, centrifuging, washing with ethanol and deionized water, and drying to obtain epoxy-modified bentonite; (2) Adding ethanol solvent, deionized water solvent, 11-aminoundecanoic acid, epoxy-modified bentonite and sodium carbonate in a mass ratio of 2000:1400:180:100:10 into a reaction container in sequence, stirring and mixing evenly, and performing a ring-opening reaction at 50° C. for 18 hours. After the reaction is completed, washing with deionized water and methanol, and drying to obtain amino acid-modified bentonite; (3) adding toluene solvent, amino acid-modified bentonite, p-toluenesulfonic acid and isosorbide dodecanoate in a mass ratio of 1500:100:3:68 into a reaction container, heating the mixture in a nitrogen atmosphere at 155° C. for 14 hours to cause an esterification reaction. After the reaction is completed, cooling the mixture, washing with sodium bicarbonate solution and deionized water, separating and drying the mixture to obtain isosorbide ester-grafted bentonite; (4) Polyvinyl chloride, isosorbide grafted bentonite, calcium stearate and polysiloxane in a mass ratio of 100:18:1.5:0.8 were added to a reaction container in sequence. After premixing at 100° C., the mixture was transferred to a twin-roll mill for melt blending at a temperature of 125° C. for 6 min. After blending, the mixture was hot-pressed on a flat vulcanizer and cooled to obtain isosorbide grafted bentonite modified polyvinyl chloride. Example 3
[0019] (1) adding ethanol solvent, nano-bentonite and 3-glycidyloxypropyltrimethoxysilane in a mass ratio of 4500:100:480 into a reaction container, uniformly dispersing by ultrasonication, and carrying out a modification reaction at 70°C for 32 hours in a nitrogen atmosphere. After the reaction is completed, centrifuging, washing with ethanol and deionized water, and drying to obtain epoxy-modified bentonite; (2) Adding ethanol solvent, deionized water solvent, 11-aminoundecanoic acid, epoxy-modified bentonite and sodium carbonate in a mass ratio of 2600:1800:220:100:12 into a reaction container in sequence, stirring and mixing evenly, and performing a ring-opening reaction at 55° C. for 24 hours. After the reaction is completed, washing with deionized water and methanol, and drying to obtain amino acid-modified bentonite; (3) adding toluene solvent, amino acid-modified bentonite, p-toluenesulfonic acid and isosorbide dodecanoate in a mass ratio of 1800:100:4:75 into a reaction container, heating the mixture in a nitrogen atmosphere at 165° C. for 15 hours to cause an esterification reaction. After the reaction is completed, cooling the mixture, washing with sodium bicarbonate solution and deionized water, separating and drying the mixture to obtain isosorbide ester-grafted bentonite; (4) Polyvinyl chloride, isosorbide grafted bentonite, calcium stearate and polysiloxane in a mass ratio of 100:22:2:1.2 were added to a reaction container in sequence. After premixing at 110° C., the mixture was transferred to a twin-roll mill for melt blending. The melt blending temperature was 135° C. and the melt blending time was 6 min. After blending, the mixture was hot-pressed on a flat vulcanizer. After cooling, isosorbide grafted bentonite modified polyvinyl chloride was obtained. Example 4
[0020] (1) adding an ethanol solvent, nano-bentonite and 3-glycidyloxypropyltrimethoxysilane in a mass ratio of 5500:100:550 to a reaction container, uniformly dispersing by ultrasonication, and carrying out a modification reaction at 75°C for 35 hours in a nitrogen atmosphere. After the reaction is completed, centrifuging, washing with ethanol and deionized water, and drying to obtain epoxy-modified bentonite; (2) Adding ethanol solvent, deionized water solvent, 11-aminoundecanoic acid, epoxy-modified bentonite and sodium carbonate in a mass ratio of 3500:2200:250:100:14 into a reaction container in sequence, stirring and mixing evenly, and performing a ring-opening reaction at 60° C. for 28 hours. After the reaction is completed, washing with deionized water and methanol, and drying to obtain amino acid-modified bentonite; (3) adding toluene solvent, amino acid-modified bentonite, p-toluenesulfonic acid and isosorbide dodecanoate in a mass ratio of 2200:100:5:85 into a reaction container, heating the mixture in a nitrogen atmosphere at 175° C. for 16 hours to cause an esterification reaction. After the reaction is completed, cooling the mixture, washing with sodium bicarbonate solution and deionized water, separating and drying the mixture to obtain isosorbide ester-grafted bentonite; (4) Polyvinyl chloride, isosorbide grafted bentonite, calcium stearate and polysiloxane in a mass ratio of 100:26:2.5:1.6 were added to a reaction container in sequence. After premixing at 120° C., the mixture was transferred to a twin-roll mill for melt blending. The melt blending temperature was 145° C. and the melt blending time was 7 min. After blending, the mixture was hot-pressed on a flat vulcanizer. After cooling, isosorbide grafted bentonite modified polyvinyl chloride was obtained. Example 5
[0021] (1) adding an ethanol solvent, nano-bentonite and 3-glycidyloxypropyltrimethoxysilane in a mass ratio of 6500:100:600 to a reaction container in sequence, uniformly dispersing by ultrasonication, and carrying out a modification reaction at 80°C for 36 hours in a nitrogen atmosphere. After the reaction is completed, centrifuging, washing with ethanol and deionized water, and drying to obtain epoxy-modified bentonite; (2) Adding ethanol solvent, deionized water solvent, 11-aminoundecanoic acid, epoxy-modified bentonite and sodium carbonate in a mass ratio of 4000:2500:280:100:15 into a reaction container in sequence, stirring and mixing evenly, and performing a ring-opening reaction at 65° C. for 30 hours. After the reaction is completed, washing with deionized water and methanol, and drying to obtain amino acid-modified bentonite; (3) adding toluene solvent, amino acid-modified bentonite, p-toluenesulfonic acid and isosorbide dodecanoate in a mass ratio of 2500:100:6:90 into a reaction container, heating the mixture in a nitrogen atmosphere at 180° C. for 18 hours to cause an esterification reaction. After the reaction is completed, cooling the mixture, washing with sodium bicarbonate solution and deionized water, separating and drying the mixture to obtain isosorbide ester-grafted bentonite; (4) Polyvinyl chloride, isosorbide grafted bentonite, calcium stearate and polysiloxane in a mass ratio of 100:30:3:2 were added to a reaction vessel in sequence. After premixing at 130° C., the mixture was transferred to a twin-roll mill for melt blending. The melt blending temperature was 150° C. and the melt blending time was 8 min. After blending, the mixture was hot-pressed on a flat vulcanizer. After cooling, isosorbide grafted bentonite modified polyvinyl chloride was obtained.
[0022] Comparative Example 1 (1) adding an ethanol solvent, nano-bentonite and 3-glycidyloxypropyltrimethoxysilane in a mass ratio of 4500:100:480 to a reaction container, dispersing them uniformly by ultrasonication, and carrying out a modification reaction at 70°C for 30 hours in a nitrogen atmosphere. After the reaction is completed, centrifuging, washing with ethanol and deionized water, and drying to obtain epoxy-modified bentonite; (2) Polyvinyl chloride, epoxy-modified bentonite, calcium stearate and polysiloxane in a mass ratio of 100:25:2:1.2 were added to a reaction container in sequence. After premixing at 110° C., the mixture was transferred to a twin-roll mill for melt blending. The melt blending temperature was 135° C. and the melt blending time was 6 min. After blending, the mixture was hot-pressed on a flat vulcanizer and cooled to obtain bentonite-modified polyvinyl chloride.
[0023] The polyvinyl chloride materials synthesized in the examples and comparative examples were subjected to impact strength tests on a ZB-901C cantilever beam impact tester. Each group was tested three times and the average value was taken. The national test standard adopted was GB / T 1843-2008.
[0024]
[0025] The polyvinyl chloride materials synthesized in the examples and comparative examples were subjected to bending strength tests on a WBE-9000B bending strength testing machine. Each group was tested three times and the average value was taken. The national test standard adopted was GB / T 1402-79.
[0026]
Claims
1. A method for preparing isosorbide grafted bentonite modified polyvinyl chloride, characterized in that: The preparation method is as follows: (1) Ultrasonic dispersion of ethanol solvent, nano-bentonite and 3-glycidyloxypropyltrimethoxysilane, and a modification reaction at 60-80° C. for 24-36 hours in a nitrogen atmosphere, to obtain epoxy-modified bentonite after the reaction is completed; (2) Ethanol and deionized water are mixed evenly, and then 11-aminoundecanoic acid, epoxy-modified bentonite and sodium carbonate are added, and the mixture is stirred and mixed evenly to cause a ring-opening reaction. After the reaction is completed, amino acid-modified bentonite is obtained; (3) Toluene solvent, amino acid modified bentonite, p-toluenesulfonic acid and isosorbide dodecanoate are mixed evenly. The molecular formula of isosorbide dodecanoate is C 18 H 32 O5, heating in a nitrogen atmosphere to cause an esterification reaction, and after the reaction is completed, isosorbide ester-grafted bentonite is obtained; (4) Premixing polyvinyl chloride, isosorbide grafted bentonite, calcium stearate and polysiloxane at 90-130° C. After premixing, transferring to a twin-roll plasticizer for melt blending, after blending, hot pressing on a flat vulcanizer, and cooling to obtain isosorbide grafted bentonite modified polyvinyl chloride.
2. The method for preparing an isosorbide grafted bentonite modified polyvinyl chloride according to claim 1, characterized in that: In the step (1), the mass ratio of ethanol, nano-bentonite and 3-glycidyloxypropyltrimethoxysilane is 2500-6500:100:350-600.
3. The method for preparing an isosorbide grafted bentonite modified polyvinyl chloride according to claim 1, characterized in that: In the step (2), the mass ratio of ethanol, deionized water, 11-aminoundecanoic acid, epoxy-modified bentonite and sodium carbonate is 1500-4000:1000-2500:150-280:100:8-15.
4. The method for preparing an isosorbide grafted bentonite modified polyvinyl chloride according to claim 1, characterized in that: The temperature of the ring-opening reaction in step (2) is 45-65° C., and the time of the ring-opening reaction is 15-30 h.
5. The method for preparing an isosorbide grafted bentonite modified polyvinyl chloride according to claim 1, characterized in that: In the step (3), the mass ratio of toluene solvent, amino acid-modified bentonite, p-toluenesulfonic acid and isosorbide dodecanoate is 1200-2500:100:2-6:60-90.
6. The method for preparing an isosorbide grafted bentonite modified polyvinyl chloride according to claim 1, characterized in that: The temperature of the esterification reaction in step (3) is 150-180° C., and the time of the esterification reaction is 12-18 hours.
7. The method for preparing an isosorbide grafted bentonite modified polyvinyl chloride according to claim 1, characterized in that: In the step (4), the mass ratio of polyvinyl chloride, isosorbide grafted bentonite, lubricant calcium stearate and defoaming agent polysiloxane is 100:15-30:1-3:0.5-2.
8. The method for preparing an isosorbide grafted bentonite modified polyvinyl chloride according to claim 1, characterized in that: The temperature of melt blending in step (4) is 120-150° C., and the time of melt blending is 5-8 min.
Citation Information
Patent Citations
Diatomite modified polyvinyl chloride synthetic leather and manufacturing method thereof
CN102995445B